2018
DOI: 10.1152/japplphysiol.00277.2018
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of vitamin C or protandim on skeletal muscle adaptation to exercise

Abstract: Maintaining proteostasis is a key mechanism for preserving cell function. Exercise-stimulated proteostasis is regulated, in part, by redox-sensitive signaling. Several studies suggest that supplementation with exogenous antioxidants blunts exercise-induced cellular adaptations, although this conclusion lacks consensus. Our group uses a fundamentally different approach to maintain redox balance by treatment with bioactive phytochemicals to activate the transcription factor nuclear factor (erythroid-derived 2)-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 60 publications
0
28
1
Order By: Relevance
“…Alternatively, abrogating training‐induced improvements in skeletal muscle oxidative potential reciprocally blunts improvements in cardiorespiratory fitness, endurance capacity, and, sometimes, measures of whole‐body health. Supplementation of exogenous vitamin C with exercise training can blunt mitochondrial biogenesis in skeletal muscle (Bruns et al, ; Gomez‐Cabrera et al, ) and minimize improvements in VO 2max and/or endurance performance in both humans and rats (Gomez‐Cabrera et al, ). Diminished skeletal muscle mitochondrial protein is reported to parallel increases in heart rate, ventilation, respiratory exchange ratio, and blood lactate concentrations at the same absolute submaximal exercise intensity following 84 days of detraining (Coyle, Martin, Bloomfield, Lowry, & Holloszy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, abrogating training‐induced improvements in skeletal muscle oxidative potential reciprocally blunts improvements in cardiorespiratory fitness, endurance capacity, and, sometimes, measures of whole‐body health. Supplementation of exogenous vitamin C with exercise training can blunt mitochondrial biogenesis in skeletal muscle (Bruns et al, ; Gomez‐Cabrera et al, ) and minimize improvements in VO 2max and/or endurance performance in both humans and rats (Gomez‐Cabrera et al, ). Diminished skeletal muscle mitochondrial protein is reported to parallel increases in heart rate, ventilation, respiratory exchange ratio, and blood lactate concentrations at the same absolute submaximal exercise intensity following 84 days of detraining (Coyle, Martin, Bloomfield, Lowry, & Holloszy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the effects of exogenous antioxidants, such as vitamin C, on muscle quality and oxidative stress. Vitamin C supplementation improves muscle function in at least one model of aged muscle (Ryan et al., 2010), but vitamin C is known to inhibit the redox signaling that leads to positive mitochondrial responses (Gomez-Cabrera et al., 2008; Paulsen et al., 2014; Bruns et al., 2018). Meta-analyses investigating the efficacy of long-term vitamin C supplementation conclude that supplementation actually increases the risk for disease and mortality (Bjelakovic et al., 2012).…”
Section: Non-exercise Treatments Of Sarcopeniamentioning
confidence: 99%
“…Other strategies targeting antioxidant mechanisms are promising though. For example, studies using a purported Nrf2 activator that increases endogenous antioxidants produces lifespan in male mice (Strong et al., 2016) and enhances protein synthesis during aerobic exercise training (Bruns et al., 2018).…”
Section: Non-exercise Treatments Of Sarcopeniamentioning
confidence: 99%
“…As highlighted, exogenous antioxidant supplementation seems to abrogate many of the mitohormetic effects of exercise. However, there appears to be some additive effect of improving cellular antioxidant capacity to exercise, as demonstrated by our work in which Nrf2 activators enhanced mitochondrial proteostasis in active rats [134] and increased proteostatic mechanisms in the skeletal muscle of older adults [135]. However, it remains unclear how a Nrf2 activator affects redox homeostasis.…”
Section: Gaps and Future Directionsmentioning
confidence: 95%
“…Our lab has demonstrated that treatment with Protandim protects coronary endothelial cells and cardiomyocytes from oxidative stress challenges [132,133]. Again, in contrast to exogenous antioxidant supplements, treatment with Protandim also enhanced proteostatic mechanisms and permitted the mitohormetic adaptations to physical activity [134]. Finally, our lab has demonstrated that treatment with a similar phytochemical Nrf2 activator enhanced the proteostatic maintenance of skeletal muscle contractile proteins in sedentary, healthy older adults [135].…”
Section: Targeting Nrf2 As a Complementary Or Alternative Approachmentioning
confidence: 99%